Trade compliance management: exploring the role of in-house trade compliance - Tirronen, Eino (My University, 2023)
The study aims to explore the role of in-house trade compliance and how it operates in multinational companies. As such, the study's main research question is “What is the role of in- house trade compliance in multinational companies?”. Trade compliance oversees that business activities comply with regulatory requirements. In addition, trade compliance activities include optimization of supply chains. The in-house teams are involved in activities such as tariff classification, incoterms consultation, preferential treatment activities, license management, export controls, customs management, screening, and valuation. However, academic research on this topic remains relatively limited despite the acknowledged importance of trade compliance to efficient trading operations and global supply chains. Therefore, this study aims to address this research gap and provide insights into the role of in-house trade compliance. Based on the study results, in-house trade compliance is both operational and advisory, and companies often emphasize the role of automation and outsourcing in their trade compliance functions. Automation ensures that human error is limited and errors are noticed proactively. Outsourcing releases resourced for more consulting work. However, compliance responsibility remains with the company, and the management level should be in-house. As such, it is common for in-house teams to perform audits and spot checks on reported documentation. A common approach to in-house trade compliance is to have a global team overseeing global guidelines and area-specific teams or managers to support and implement compliance in other departments. However, the approach to in-house trade compliance may vary across different companies and industries, and each company may have its unique perspective on trade compliance. Therefore, it is important for companies to carefully consider their specific trade compliance requirements and tailor their approach accordingly.
Keywords: Trade compliance, customs compliance, compliance management, customs management, customs, compliance automation, supply chain risk management, supply chain optimization, compliance outsourcing